Allele-specific DNA methylation of disease susceptibility genes in Japanese patients with inflammatory bowel disease - Chiba, Hirofumi; Kakuta, Yoichi; Kinouchi, Yoshitaka; Kawai, Yosuke; Watanabe, Kazuhiro; Nagao, Munenori; Naito, Takeo; Onodera, Motoyuki; Moroi, Rintaro; Kuroha, Masatake; Kanazawa, Yoshitake; Kimura, Tomoya; et al. (PLOS ONE, 2018)
Background Inflammatory bowel disease (IBD) has an unknown etiology; however, accumulating evidence suggests that IBD is a multifactorial disease influenced by a combination of genetic and environmental factors. The influence of genetic variants on DNA methylation in cis and cis effects on expression have been demonstrated. We hypothesized that IBD susceptibility single-nucleotide polymorphisms (SNPs) regulate susceptibility gene expressions in cis by regulating DNA methylation around SNPs. For this, we determined cis-regulated allele-specific DNA methylation (ASM) around IBD susceptibility genes in CD4+ effector/memory T cells (Tem) in lamina propria mononuclear cells (LPMCs) in patients with IBD and examined the association between the ASM SNP genotype and neighboring susceptibility gene expressions. Methods CD4+ effector/memory T cells (Tem) were isolated from LPMCs in 15 Japanese IBD patients (ten Crohn's disease [CD] and five ulcerative colitis [UC] patients). ASM analysis was performed by methylation-sensitive SNP array analysis. We defined ASM as a changing average relative allele score (ΔRAS¯) >0.1 after digestion by methylation-sensitive restriction enzymes. Among SNPs showing ΔRAS¯ >0.1, we extracted the probes located on tag-SNPs of 200 IBD susceptibility loci and around IBD susceptibility genes as candidate ASM SNPs. To validate ASM, bisulfite-pyrosequencing was performed. Transcriptome analysis was examined in 11 IBD patients (seven CD and four UC patients). The relation between rs36221701 genotype and neighboring gene expressions were analyzed. Results We extracted six candidate ASM SNPs around IBD susceptibility genes. The top of ΔRAS¯ (0.23) was rs1130368 located on HLA-DQB1. ASM around rs36221701 (ΔRAS¯ = 0.14) located near SMAD3 was validated using bisulfite pyrosequencing. The SMAD3 expression was significantly associated with the rs36221701 genotype (p = 0.016). Conclusions We confirmed the existence of cis-regulated ASM around IBD susceptibility genes and the association between ASM SNP (rs36221701) genotype and SMAD3 expression, a susceptibility gene for IBD. These results give us supporting evidence that DNA methylation mediates genetic effects on disease susceptibility.